Comparação de ácidos naftênicos por ressonância magnética nuclear e ouras técnicas analísticas - Corti, Mayara Modenesi (2016)
Naphthenic acids are a diverse group of carboxylic acids present in petroleum. The presence of these compounds in the oil is harmful to the refining equipment since according to oil’s composition, they can cause corrosion, emulsions and precipitates formation, consequently, leading to great losses in production. Corrosion in oils processing is related to sulfur compounds content in the oil and to the type of acid present, being the latter of smaller chain and having the acidic hydrogen more available to attack. Precipitates formation is associated to the acids transformation (generally of longer chain) in poorly soluble salts, which deposit in the transfer ducts. NMR technique was used in this work to differentiate the types of naphthenic acids extracted from oil and calcium naphthenates. For samples extracted from oil, it was possible to observe a content of approximately 8% of aromatic hydrogens and 90% of alkyl. Among the last quantity, the large variety of Ha, Hß and H? levels indicates the structural diversity of the compounds present in the oil extracted samples. With the pH extraction increasement, it was noticed a decrease in Ha and a raise in Hß and H? contents, indicating the greater complexity of the extracted structures. For samples extracted from calcium naphthenates, contents of almost 5% of aromatic hydrogens and 95% of alkyl were observed, however, for these samples, no significant variation was noticed between the different extractions, what indicates that these compounds have similar compositions. A higher content of Hß was observed in comparison to Ha and H?, which attests these compounds have many ramifications near the aromatic ring, showing a structure with a pronounced alkyl chain, similar to that described in literature for ARN. In conclusion, it was possible to differentiate these two types of samples using NMR, since the aromatic and alkyl hydrogens contents are characteristic for each kind of naphthenic acid extracted from oil or calcium naphthenate.